Analysis of Nuclear and Diesel-Electric Submarines' Efficiency and Emission in Supporting the Modernization of Defense Armaments (KRI Nanggala 402 and USS Nautilus SSN-571) - Rendy Ananta Prasetya; Syamsul Maarif; Jonni Mahroza; Luhut Simbolon (Budapest International Research and Critics University, 2022)
All Indonesian submarines operating today use diesel-electric submarines that rely on a diesel engine as propulsion when diving and an electric generator to charge the battery while on the surface. The presence of nuclear submarines is relied upon because of their long operating life and more powerful despite their large size and must be in diving conditions. The purpose of this study was to determine the efficiency of the use of nuclear submarines against diesel-electric. The method used is a literature study to collect relevant data related to nuclear and diesel-electric submarines which is then projected to calculate efficiency based on the resulting fuel emissions. The results show that KRI Nanggala 402 as a diesel-electric submarine requires 33.75 tons of oil with CO2 emissions of 106.64 tons, while the USS Nautilus SSN-571 as a nuclear propulsion submarine requires 0.182 kg of uranium that does not produce emissions. In terms of diplomacy, the increasing challenges in developing the modernization of nuclear-based defense weapons provide space for multilateral diplomacy for peaceful purposes.